2020
DOI: 10.1007/s10552-020-01356-3
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: 20 years online with “Your Disease Risk”

Abstract: The Your Disease Risk tool (yourdiseaserisk.wustl.edu) went live to the public in January 2000 and was one of the first personalized health risk assessment sites on the Internet. Its launch marked the culmination of years of work by a large, multi-disciplinary university team whose primary goal was to translate the science on cancer prevention into accurate, engaging, and useful messages for the public. Today, 20 years on, Your Disease Risk has expanded from its initial four cancers to include 18 different too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 41 , 143 The consideration of numeracy and health literacy in the development of clinical decision tools could potentially help increase tool accessibility among patients from diverse backgrounds. Recent tools developed to address contextual factors 27 , 144 include a tool consisting of low-income resources in the region that health care providers could share with their eligible patients. 145 However, there is insufficient evidence on the use of contextual factors as inputs for risk prediction in clinical decision tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 , 143 The consideration of numeracy and health literacy in the development of clinical decision tools could potentially help increase tool accessibility among patients from diverse backgrounds. Recent tools developed to address contextual factors 27 , 144 include a tool consisting of low-income resources in the region that health care providers could share with their eligible patients. 145 However, there is insufficient evidence on the use of contextual factors as inputs for risk prediction in clinical decision tools.…”
Section: Discussionmentioning
confidence: 99%
“… 24 26 For example, clinical decision tools for bladder cancer include contextual factors such as occupational exposures and drinking well-water to identify high-risk individuals. 27 …”
mentioning
confidence: 99%
“…We chose to study risk skepticism in the context of type 2 diabetes because diabetes is a severe and common disease, 32,33 is modifiable through health behavior change, 34 and has risk assessment tools that are understudied. Although there are several type 2 diabetes risk assessment tools available online (e.g., Waters et al 2 and Colditz 35 ), there is also a dearth of research describing people's responses to being provided personalized estimates about their risk of developing type 2 diabetes. The only exception 36 reported that providing personalized prediabetes risk estimates prompted participants' risk perceptions to become more accurate, but only among individuals who initially underestimated their risk.…”
Section: Objectives and Hypothesesmentioning
confidence: 99%